The Impact of Perceived Competency on Motivation and Innovative ‎Working Behavior Case Study of Lecturers in Vietnam - Pham, Chinh D. (International Journal of Accounting and Economics Studies, 2025)
This study aims to examine the influence of perceived competence on the motivation and innovative work ‎behavior of university lecturers in Vietnam. A mixed-methods research approach was employed, incorporating focus group discussions to refine the scale to suit the context and structural equation modeling (SEM) analysis to test the hypotheses. Data were collected from 459 university lecturers through a convenience sampling method. The ‎results showed that all hypotheses were statistically significant. Specifically, perceived competence (PEC) ‎directly and indirectly affects innovative work behavior (IWB) through two mediating variables: intrinsic ‎motivation (INM) and extrinsic motivation (EXM). The study provides empirical evidence on the mediating ‎role of motivation and offers managerial implications for educational leaders to promote innovation in the ‎university environment in Vietnam, thereby improving the effectiveness of teaching, research and knowledge ‎transfer in the context of global integration‎.